2021
DOI: 10.1111/ijac.13709
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning the lattice constant of cubic pyrochlore compounds

Abstract: Pyrochlores, with a general formula A 2 B 2 X 7 , are promising candidates in many potential applications due to their wide varieties of physical properties. Different combinations of cations and anions in the crystal structure enable the tailoring of their properties and functionalities. For cubic pyrochlores, the lattice constant, a, is an integrated result of stoichiometry, ionic radii, and electronegativities of alloying elements.It also has significant impacts on stabilities, electronic structures, ionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Brgoch et al 30 developed a support vector regression algorithm based on 134 experimentally measured temperature-dependent Eu 3+ emission data points to rapidly predict the thermal quenching temperature. The lattice constants of pyrochlores were successfully predicted by Zhang et al 31 using a Gaussian process regression (GPR) model with electronegativities and ionic radii as descriptors. The aforementioned researchers have achieved certain milestones; however, KNN provides better results when dealing with sparse and scattered data.…”
Section: Introductionmentioning
confidence: 99%
“…Brgoch et al 30 developed a support vector regression algorithm based on 134 experimentally measured temperature-dependent Eu 3+ emission data points to rapidly predict the thermal quenching temperature. The lattice constants of pyrochlores were successfully predicted by Zhang et al 31 using a Gaussian process regression (GPR) model with electronegativities and ionic radii as descriptors. The aforementioned researchers have achieved certain milestones; however, KNN provides better results when dealing with sparse and scattered data.…”
Section: Introductionmentioning
confidence: 99%
“…Brendan et al have investigated the relationship between the structural and bonding energy in lanthanide pyrochlore oxides (Sn 2 O 7 ) and found that the position parameter of the oxygen vacancies is inversely proportional to the lattice parameter. Recently, Zhang et al have reported on the machine learning (ML) methods to determine lattice constants of different multi-substitutional pyrochlores in the range of 9-11 Å [17]. Moreover, the pyrochlore stannate (Ce 2 Sn 2 O 7 ) demonstrated a temperature-dependent anisotropic nature [18].…”
Section: Introductionmentioning
confidence: 99%
“…8–10 Pyrochlore-based oxides with the general formula A 2 B 2 O 7 have been considered good candidates for highly sought application areas such as superconductors, multiferroic materials, catalysts, and photoelectronic devices due to their high ionic conductivity and low electronic conductivity. 11,12 Among them, Nb-based pyrochlore semiconductors have been applied in various photocatalysts because of their excellent ability to transfer photogenerated electron–hole pairs. Importantly, Nb-based photocatalysts have more negative conduction band (CB) levels, which consist of a Nb 4d orbital as opposed to a Ti 3d orbital, giving the photogenerated electrons strong reducing capability.…”
Section: Introductionmentioning
confidence: 99%